WORK ENGAGEMENT KARYAWAN MRN TERHADAP IMPLEMENTASI APLIKASI DATA ANALISIS SDM - Meirlyn Mewengkang; Hana Panggabean (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2016)
Corporate Human Resources (CHR) is a division at MRN that has a role to manage human resources in the company. MRN is a holding company, supervising its business units, and through its business units, mostly operates in mass media. In line with its vision, CHR MRN is highly expected to provides data analysis to help higher management in making strategic decision. But in fact, most of CHR’s employee only provides documentation data. This kind data can’t be used for strategic decision making in Human Recources. This situation shows there is indication of work engagement problem, where the employee’s lack of willingness to make and provide analysis data. The data collection method used Utrecht Work Engagement Scale-17 and 55 respondents at CHR’s MRN participated in this research. Data analysis technique used in this research is anova one-way. The result of this research shows that 69% CHR’s employees have work engagement in the middle level, an there is 18% in the low level, and the rest is 13 % in the high level. Result of statistic calculation shows that there is significant difference in demographic data, such as working period, where group of employees that have 1-5 years working period have lowest score comparing with other group of employees. Considering the importance of increasing work engagement to improve company effectiveness, the suggested intervention designs are socialization program, employee work plan form, feedback giving from superior, monitoring form.